2022
DOI: 10.1029/2021jd036044
|View full text |Cite
|
Sign up to set email alerts
|

When Will Humanity Notice Its Influence on Atmospheric Rivers?

Abstract: Atmospheric rivers (ARs), river-like plumes of intense atmospheric moisture transport (Newell et al., 1992) typically associated with extratropical cyclones (Zhang et al., 2019), are known for their great socioeconomic impacts worldwide. ARs occur less than 10% of the time but account for more than 30% of the annual precipitation over some populated mid-latitude regions, such as the West Coast of the United States and Western Europe, which indicates both their water resource value and the potential hazards of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…This paper uses a five‐member subset of the larger thirty‐member SPEAR ensemble and uses IVT and AR statistics as calculated by Tseng et al. (2022). Tseng et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper uses a five‐member subset of the larger thirty‐member SPEAR ensemble and uses IVT and AR statistics as calculated by Tseng et al. (2022). Tseng et al.…”
Section: Methodsmentioning
confidence: 99%
“…We are therefore confident in SPEAR's ability to resolve both local climate trends in California and global circulation patterns relevant to ARs. This paper uses a five-member subset of the larger thirty-member SPEAR ensemble and uses IVT and AR statistics as calculated by Tseng et al (2022). Tseng et al (2022) have demonstrated that the AR statistics derived from a single ensemble member are still representative of the entire large ensemble, provided the analysis period is sufficiently long (≥30 years), given the short memory of AR events from season to season.…”
Section: Climate Model Projectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The version of SPEAR we analyze here [SPEAR_MED in the notation of Delworth et al (2020) but referred here as SPEAR for simplicity] has 33 vertical levels with a model top at 1 hPa in the atmosphere, a horizontal grid spacing of 0.5 • in the atmosphere and land components, and approximate 1 • horizontal spacing (telescoping to 0.33 • meridional spacing near the equator) in the ocean and sea ice components. SPEAR has been successfully used for studies of climate variability, prediction, and projection spanning subseasonal (Xiang et al, 2022), seasonal (Bushuk et al, 2021(Bushuk et al, , 2022Tseng et al, 2021;Jia et al, 2022), decadal (Joh et al, 2022), and multidecadal (Murakami et al, 2020;Pascale et al, 2020;Tseng et al, 2022) timescales.…”
Section: Spear Simulationsmentioning
confidence: 99%